Cloning of the two chalcone flavanone isomerase genes from Petunia hybrida: coordinate, light-regulated and differential expression of flavonoid genes. - van Tunen, A J (1988)
In this paper we report the isolation of cDNA clones encoding the flavonoid-biosynthetic enzyme chalcone flavanone isomerase (CHI) from Petunia hybrida. A nearly full size cDNA clone, isolated from a corolla-specific expression library, was characterized by sequence analysis. Using this CHI cDNA and the previously cloned flavonoid-specific chalcone synthase (CHS) cDNA we show that CHI and CHS genes are coordinately and tissue-specifically expressed in a developmental and light-regulated manner. Furthermore, coordinate induction of both mRNAs is observed after continuous irradiation of Petunia plantlets with UV light, probably as part of the plants UV defence mechanism. The two CHI genes, denoted A and B, were isolated from a genomic library of the Petunia inbred line V30. Both genes are transcriptionally active: gene A is transcribed in corolla, tube and UV-irradiated plantlets (1.0 kb mRNA), whereas gene B is only transcribed in immature anthers (1.0 kb mRNA). In combination with Southern blot analysis these data implicate the presence of two distinct non-allelic CHI genes in the genome of the P. hybrida line V30. Unexpectedly, mature anthers accumulate a 0.3 kb larger CHI RNA. This RNA is transcribed from CHI gene A and has a 0.3 kb 5' extension relative to the gene A transcript found in corolla tissue. Furthermore it is neither coordinately expressed with CHS mRNA nor UV inducible. Its biological function is still obscure, since no active CHI enzyme could be demonstrated in the same tissue.